KERAGAMAN JENIS HAMA KUTU PUTIH PADA TANAMAN SINGKONG DI KOTA ENDE - Wilfridus Lena; Yustina Maria Silvia Wonga Puu (AGRICA, 2018)
This study aims to determine the type of white lice (Mealybug) pest associated with cassava plants (ManihotesculentaCrantz) in Ende Regency. The observation variables used included the identification of the hamlet species found in the field and calculating the level of diversity, abundance, dominance, similarity / similarity and intensity of pest attacks. The results showed that the diversity index for Nangapanda District was 1.052 (medium), abundance of 0.243 (low), and dominance index of 0.465 (moderate). Ende District diversity index 0.953 (low), abundance 0.348 (low), and dominance index 0.428 (moderate). Ende Selatan Subdistrict diversity index is 0.927 (low), abundance is 0.351 (low), and dominance index is 0.438 (moderate). In NdonaSubdistrict the diversity index is 0.683 (low), abundance is 0.358 (low), and dominance is 0.397 (moderate). For the similarity / similarity type index between Nangapanda sub-district and other sub-districts which is 85.71%. Similarity / similarity between Ende District and three other Sub-districts, namely 85.71%, 100% and 100%. The similarity between Ende Selatan District and the other three Sub-districts is 85.71%, 100% and 100%. The similarity between NdonaSubdistrict and the other three Subdistricts is 85.71%, 100% and 100%. While the intensity of pest damage in each Subdistrict was 47.7%, in Ende District 32.5%, South Ende 25% and Ndona District 38.33%.